Custos de transação no financiamento bancário à infraestrutura - Silva, Maurício Alexandre (2019)
The studies presented here propose a description of transaction costs present in bank financing to infrastructure and, in addition, a quantitative analysis of how they behave based on some independent variables, such as the number of debtors / financed and the type or origin of the financing bank. including development banks, Brazilian commercial banks and international banks that operate in Brazil. The results reveal that the number of debtors / financed influences some transaction costs, possibly due to the uncertainty that the increase in the number of debtors inserts in each contract, causing the financing banks to increase costs, to cover the associated risk. In addition, they reveal that there is a clear difference in costs and financing criteria, depending on the type of financing bank, among those mentioned above. For example, international banks with a presence in Brazil choose larger entrepreneurs and, in general, have higher financing costs. The studies contribute to deepen the knowledge about large bank financing, such as those that make infrastructure projects feasible, in addition to presenting tools that enable administrators, such as debtors / financed, to obtain a more comprehensive view as to what costs they are exposed, as well how to better understand under what conditions they fluctuate.